Design of a Digital Electronic Tool for Evaluating the Quality of Inpatient Medical Records - Widasari, Immaculata Vettha Sarasvati; Rusdi, Achmad Jaelani; Suhariyono, Untung Slamet; Choiriyah, Ana (PROMOTOR, 2025)
This study aims to develop a digital-based qualitative analysis form to assist in the evaluation process of inpatient medical records at Mardi Waluyo Regional General Hospital in Blitar City. Current documentation practices are still done manually, resulting in medical records that are often incomplete and inconsistent. This study uses a qualitative descriptive method with a simple Research and Development (R&D) approach. Qualitative analysis was conducted to assess the completeness and consistency of medical records, while the R&D approach was used in designing the electronic-based qualitative analysis form. Based on 30 medical record samples, several inconsistencies were identified, particularly in the completeness and consistency of nursing care notes. This digital form was developed to simplify the assessment process, improve accuracy, and reduce documentation errors. Equipped with automatic notifications and an Excel export feature, this form facilitates a more structured and efficient qualitative analysis process. This innovation is expected to support service quality improvement and be further developed into a more complex electronic qualitative analysis system in the future.